Health-Related Quality of Life in Cancer Survivors with Chemotherapy-Induced Peripheral Neuropathy: A Randomized Clinical Trial. (26th August 2021) - Bao, Ting; Baser, Raymond; Chen, Connie; Weitzman, Matthew; Zhang, Yi Lily; Seluzicki, Christina; Li, Qing Susan; Piulson, Lauren; Zhi, W. Iris
Abstract : Background: Chemotherapy-induced peripheral neuropathy (CIPN) is a common, debilitating adverse effect of neurotoxic chemotherapy that significantly worsens the quality of life of cancer survivors. Materials and Methods: Survivors of solid tumors with persistent moderate-to-severe CIPN defined as numbness, tingling, or pain rated ≥4 on an 11-point numeric rating scale (NRS) were randomized in a 1:1:1 ratio to 8 weeks of real acupuncture (RA) versus sham acupuncture (SA) versus usual care (UC). We previously reported the primary endpoint (NRS); here we report the following health-related quality of life endpoints: Functional Assessment of Cancer Therapy/Gynecologic Oncology Group-Neurotoxicity (FACT/GOG-Ntx), Hospital Anxiety and Depression Scale (HADS), Insomnia Severity Index (ISI), and Brief Fatigue Inventory (BFI). For each endpoint, the mean changes from baseline and 95% confidence intervals were estimated within each arm and compared between arms using linear mixed models. Results: We enrolled 75 survivors of solid tumors with moderate-to-severe CIPN into the study. Compared with baseline, at week 8, FACT/GOG-Ntx, HADS anxiety, and ISI scores significantly improved in RA and SA, but not in UC. Compared with UC, at week 8, FACT/GOG-Ntx scores significantly increased in RA and SA arms indicating improved CIPN-related symptoms and quality of life ( p  = .001 and p  = .01). There was no statistically significant difference between RA and SA. There was no difference in HADS depression or BFI among RA, SA, and UC at weeks 8 and 12. Conclusion: Acupuncture may improve CIPN-related symptoms and quality of life in cancer survivors with persistent CIPN. Further large sample size studies are needed to delineate placebo effects. Implications for Practice: The authors conducted a randomized sham acupuncture- and usual care-controlled clinical trial to evaluate the impact of acupuncture on health-related quality of life outcomes in patients with solid tumors with chemotherapy-induced peripheral neuropathy (CIPN). Statistically significant improvements in quality of life, anxiety, insomnia, and fatigue were achieved with 8 weeks of real acupuncture when compared with baseline, without statistically significant differences between real and sham acupuncture. These findings suggest that acupuncture may be effective for improving CIPN-related symptoms and quality of life and reducing anxiety and insomnia in cancer survivors with persistent CIPN, with further study needed to delineate placebo effects. Abstract : Acupuncture is a promising and safe nonpharmacological approach to potentially address the unmet need for an effective treatment of chemotherapy-induced peripheral neuropathy. This article reports the results of a randomized sham acupuncture- and usual care-controlled clinical trial to evaluate the effect of acupuncture on health-related quality of life outcomes in patients with solid tumors dealing with chemotherapy-induced peripheral neuropathy.